Analysis of N-Acy-L-homoserine lactones (AHLs) in wastewater treatment systems using SPE-LLE with LC-MS/MS. (15th June 2020) - Huang, Shujuan; Zhang, Hui; Albert Ng, Tze Chiang; Xu, Boyan; Shi, Xueqing; Ng, How Yong
Abstract: The occurrence and distribution of N-acyl homoserine lactones (AHLs) in membrane bioreactors (MBRs) treating wastewater has garnered much attention as they have been shown to play critical role in biofouling. There is a need to develop a single method capable of analysing AHLs in various wastewater with comparable and reliable performance. A novel and robust method was proposed for trace analysis of 11 AHLs in wastewater treatment systems treating domestic and industrial wastewater. This method utilised solid phase extraction (SPE) to extract AHLs from wastewater followed by liquid-liquid extraction (LLE) to extract AHLs from the SPE eluant, and used N-heptanoyl-dl -homoserine lactone (C7-HSL) as an internal standard. There was no need to prepare matrix-matched calibration curve for accurate quantification of AHLs in the liquid chromatography tandem mass chromatography (LC-MS/MS) analysis. The developed method was validated with six different types of domestic and industrial wastewater with regard to AHLs recoveries and matrix effects. For treated domestic and industrial wastewater, the relative recoveries ranged from 75% to 130% and the matrix effects ranged from 89% to 122%. This method exhibited remarkable improvement compared with single SPE. The results also indicated that inclusion of LLE after SPE could effectively alleviate matrix effects, which may be because of the removal of relatively hydrophilic interferences by using dichloromethane to extract AHLs from the SPE eluant composing of methanol and water. The limits of detection of the AHLs were all below 5 ng/L for the tested wastewater samples. The developed method of SPE-LLE with LC-MS/MS was applied to analyse AHLs in four lab-scale and one pilot-scale wastewater treatment systems. Wide spectrum of AHLs with alkanoyl chains ranging from C4 to C14 were detected with concentrations ranging from 2.7 to 299.2 ng/L. This method is capable of identifying and quantifying trace levels of AHLs in various wastewater treatment systems and can help us better understand the mechanisms of AHL-mediated quroum sensing in various wastewater treatment systems. Graphical abstract: Image 1 Highlights: SPE-LLE is a breakthrough for AHLs quantification in complex wastewater. SPE-LLE process alleviates matrix effects effectively compared to single SPE. Matrix-matched calibration curve is not required for accurate analysis of AHLs. LODs of the AHLs were below 5 ng/L for domestic and industrial wastewater. Wide spectrum (C4 to C14) of AHLs were detected in 5 wastewater treatment systems.